Efeito de tratamentos isotérmicos na microestrutura e corrosão intergranular do aço inoxidável duplex UNS S32205 - Quadros, Pedro Victorio Caetano Abrantes de (2023)
Duplex stainless steels are two-phase metal alloys with similar proportions of ferrite and austenite, which gives properties such as high mechanical and corrosion resistance to the material. Due to its characteristics, this steel has application at the industries of pulp and paper, petrochemical, etc. However, depending on their operational environment, these alloys require thermal or thermochemical treatments, and, when subjected to temperatures in the range of 300 to 1000°C, this material can suffer changes in its properties, because of changes in its microstructure. These transformations include the variation in the proportion of ferrite and austenite, as well as the precipitation of intermetallic phases, especially sigma. The precipitation of these deleterious phases can impair corrosion resistance, since, due to their composition being rich in chromium, it impoverishes the matrix of this element, consequently, making it susceptible to intergranular corrosion. Therefore, this work aims to evaluate the isothermal treatments, at temperatures from 850 to 1150°C, on the microstructure and intergranular corrosion of duplex stainless steel UNS S32205. Thus, through the technique of quantitative stereology, the proportions of the phases were obtained for each isothermal treatment condition. The results indicated the presence of the sigma phase in the samples treated at temperatures below 1000°C, with the highest volumetric proportion in the one submitted to 850°C. In addition, for the pieces treated from 1000°C, it was noted that the higher the temperature, the more equiaxed the grains and the higher the ferrite fraction. Additionally, to determine the degree of sensitization, DL-EPR assays were designed in sulfuric acid solution at concentrations of 0.5, 1.5 and 2.5 mol/L with addition of 1 mol/L of hydrochloric acid. From the corrosion tests, sensitization was verified only for the condition submitted to isothermal treatment at 850°C in electrolyte composed of H2SO4 2.5 mol/L and Hcl 1 mol/L. By SEM, it was noted that intergranular corrosion occurred preferentially at the sigma phase interfaces. Finally, through the EDS technique, it was observed that the precipitation of the sigma phase did not alter the chemical composition of ferrite and austenite, besides showing that there were no changes in the percentage by weight of the elements chromium, nickel and molybdenum of the three phases after the DL-EPR assays.